Digital Index of The Fingers with Digital Clubbing: An objective measurement to diagnose clubbed finger - Djojodibroto, Rahardjo Darmanto; Said, Asri; AS, Nurul Shahirah; Sim, Chun Yang (Perhimpunan Dokter Paru Indonesia (PDPI), 2019)
Abstract Introduction: Digital clubbing can often be found as a clinical sign in patients with various underlying diseases. However, early signs of clubbing are often overlooked. To determine the Digital Index values from the fingers with clinical features of clubbing of varies conditions background. Method: This was a prospective, case-series, investigator-initiated observation by morphometry, conducted in Kuching General Hospital, Malaysia along 6 months duration. Participants were 46 patients with varies stage of clubbing of varies conditions and diseases. We measured the finger at the circumference of the Nail Fold and Distal Interphalangeal joint which determined the value of the Digital Index of a population with finger clubbing. Results: The value of the Digital Index of finger clubbing in this study was 9.89±0.68 (Mean±SD) for male and 9.87±0.39 (Mean±SD) for female. The value of the Digital Index of finger clubbing for all subjects together was 9.88±0.56 (Mean±SD) with a range of 8.43 to 11.26. Conclusion: Early clubbing often be overlooked. To avoid such condition, the physician should examine the fingers as a routine procedure. Measurement of Digital Index can be recommended to detect early clubbing. (J Respir Indo. 2019; 39(3):196-203) Keywords: Hippocratic fingers, digital clubbing, finger clubbing, watch glass nails, drumstick finger.